Influence of rearing temperature and feed format in the development of the pendulous crop in broilers - Almeida, Eduardo Alves [UNESP]; Silva, Flávio Henrique Aráujo; Crowe, Trever Gordon; Macari, Marcos [UNESP]; Furlan, Renato Luis [UNESP] (Elsevier, 2018)
The pendulous crop is characterized by excessive distension of the crop musculature, compromising the bird's productivity and welfare. The etiology is still unknown, but it is believed that factors related to the birds' handling might be related to its incidence. The study was conducted in 2 environmental chambers. One was maintained at a comfortable temperature, while the other was set at a much lower temperature. In each chamber, animals were divided into 16 experimental pens (8 received mash feed and the others received pelletized feed) with a density of 12 birds/m2 (an expected stocking density of 32- 36 kg/m2 after 42 d). The effects of rearing temperatures were evaluated in terms of broiler performance, specifically weight gain (kg), feed intake (kg), weekly feed intake (kg/wk), and feed conversion (kgfeed/kggrowth). The occurrences of pendulous crop were quantified every 2 d after the 14th day of rearing. Birds grown in thermal comfort and fed a pelletized ration were most susceptible (12%) to pendulous crop, followed by birds fed pelletized feed and reared in cold conditions (6.8%), and birds given mashed feed and reared at either temperature (about 3%). We concluded that feeding pelleted feed combined with warmer rearing temperatures may have caused some alteration of the gastrointestinal system of birds, which caused pendulous crop to be more prevalent.
Keywords: cold stress; digestive system; gut flow; pendulous crop; thermal comfort